Strategic crowding, an illness that erodes sector profitability: case pharmaceutic industry in Colombia - Rivera Rodríguez, Hugo; Malaver Rojas, Natalia (Cuadernos de Administración, 2010)
Firms in the last decade have faced a turbulent environment, characterized by increasing complexity in relationships, changes in the needs of customers, and increased uncertainty in decision making. Some companies respond to this situation using the same strategies of industry leaders, leading to a convergence process, which affects the profitability of the sector. This paper presents a methodology that allows a better way to see what happens in one sector and determine the degree of convergence